2016
DOI: 10.9738/intsurg-d-16-00003.1
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Laparoscopically-Assisted Endoscopic Appendectomy: A Major Hybrid Natural Orifice Transluminal Endoscopic Surgery Case Series in Asia

Abstract: Hybrid NOTES procedures can be performed safely using a solo-umbilical trocar. Our initial experience reveals that this hybrid technique is practically feasible and associated with minimal post-operative pain, reasonable convalescence time, and improved cosmetic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Because it does not result in surgical scar, NOTES has been receiving substantial attention from surgeons in many countries. NOTES was used not only for hysterectomy but also for adnexectomies [ 6 7 8 9 ], ectopic pregnancies [ 10 11 ], appendectomies [ 12 13 14 15 ], and cholecystectomies [ 16 17 18 ]. Recently, feasibility and technique for transvaginal NOTES liver resection was studied in a porcine model [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because it does not result in surgical scar, NOTES has been receiving substantial attention from surgeons in many countries. NOTES was used not only for hysterectomy but also for adnexectomies [ 6 7 8 9 ], ectopic pregnancies [ 10 11 ], appendectomies [ 12 13 14 15 ], and cholecystectomies [ 16 17 18 ]. Recently, feasibility and technique for transvaginal NOTES liver resection was studied in a porcine model [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Steinemann et al also stated that hybrid NOTES reduces postoperative pain and is associated with greater cosmetic satisfaction [ 17 ]. Khan et al revealed that hybrid V-NOTES appendectomy is associated with minimal post-operative pain, shorter healing time, and improved cosmetic outcomes [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Natural orifice transluminal endoscopic surgery (NOTES) has been predicted to replace conventional laparoscopy in the near future. [1][2][3][4][5][6][7][8][9][10] In addition, the transvaginal route, having typical physical and physiological benefits, [1][2][3][4][5][6][11][12][13][14][15][16] makes it the safest, as well as an immensely popular method. [1][2][3]6,[11][12][13][14][15][17][18][19][20][21][22][23][24][25][26] However, even a decade after its inception, it continues to be fraught with diverse technical hurdles such as spatial constraints, inadvertent vaginal gas-leak, compelling requirements for complex instrumentation, scarce availability and affordability, and a steep learning curve, to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]6,[11][12][13][14][15][17][18][19][20][21][22][23][24][25][26] However, even a decade after its inception, it continues to be fraught with diverse technical hurdles such as spatial constraints, inadvertent vaginal gas-leak, compelling requirements for complex instrumentation, scarce availability and affordability, and a steep learning curve, to name a few. 7,[13][14][15][16][17][18][19][20] Gas leaks from the vaginal port-rents fail to maintain adequate pneumoperitoneum and often necessitates tamponade by wet compresses. This hinders a smooth performance, leading to extended surgical times.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation